Keep Your Eyes Wide Open: On Visual- and Vision-Related Measurements to Better Understand Multiple Sclerosis Pathophysiology. Issue 1 (March 2018) - Backner, Yael; Levin, Netta
Abstract : Background: Multiple sclerosis (MS), a demyelinating disease of the central nervous system, is multifaceted. It manifests as acute episodes as well as an accumulative chronic disability; myelin involvement as well as axonal damage; local as well as global effects; and disease load elements as well as compensatory mechanisms. The visual system, with its clear structural organization and relatively direct reflection of damage, may serve as an appropriate model to study MS. Methods: In recent years, we have witnessed a blossoming in the field of visual measures in MS. Because it is impossible to cover all different aspects of these measures, we chose to focus on several hot topics in MS literature and shed light on them through studies conducted in the visual system. Results: We argue that numerous methods can be used to study axonal and demyelinating aspects of the disease. Although optical coherence tomography and static visual functions better reflect the axonal aspects of the disease, conduction velocity as measured by visual-evoked potential latencies and dynamic visual function mirrors myelin levels. We also posit that the classic disease load parameters cannot be the only means by which we assess a patient's condition. Novel imaging methods such as diffusion tensor imaging and functional magnetic resonance imaging can be used to assess the global effects of local damage on neighboring white matter and compensatory abilities of the brain. Conclusions: There have been great advances in therapeutic research in MS. However, the stratification of patients according to their prognosis and predictive outcomes in response to treatment is still in its infancy. The many facets of MS make it difficult to piece all the data together into one cohesive conclusion for the individual patient. The visual system, with our ability to assess both structure and function, offers a promising opportunity to study both pathophysiologic mechanisms and novel therapies.